Overexpression of DoUGP Enhanced Biomass and Stress Tolerance by Promoting Polysaccharide Accumulation in Dendrobium officinale - Chen, Ji; Wang, Li; Liang, Huan; Jin, Xiaowan; Wan, Jian; Liu, Fan; Zhao, Ke; Huang, Jin; Tian, Mengliang (Frontiers in Plant Science, 2020)
Uridine diphosphate glucose pyrophosphorylase (UDP-glucose pyrophosphorylase, UGPase), as one of the key enzymes in polysaccharide synthesis, plays important roles in growth and development of plants. In this study, DoUGP gene of Dendrobium officinale was overexpressed. The expression of DoUGP and genes playing roles in the same and other saccharide synthesis pathways were determined, and total soluble polysaccharide was also tested in both wild type and transgenic seedlings. Furthermore, we also performed freezing and osmotic stress treatments to determine whether overexpression of DoUGP could influence stress resistance in transgenic seedlings. Results showed that mRNA expression levels of DoUGP and its metabolic upstream and downstream genes in the transgenic seedlings were increased compared to the expression of these genes in wild type seedlings. However, CSLA family involved in biosynthesis of mannan polysaccharide was significantly repressed. The polysaccharide content of transgenic seedlings was increased compared to the content of wild type. This study aims to explore the role of DoUGP gene in polysaccharide synthesis pathway of D. officinale and provide theoretical and practical solutions for the quality improvement of the important medicinal plant D. officinale.